Implementation of the european charter of local self-government in ukrainian legislation - Shevchenko, Anatolii Yevheniiovych; Kudin, Serhii Volodymyrovych; Kapichon, Olha Hryhorivna (Scientific Publishing Center “Sci-conf.com.ua”, 2020)
The European Charter of Local Self-Government, adopted in Strasbourg on 15 October 1985 by the member States of the European Council, became the basis for international regulation of self-government in progressive countries that are members of the Council of Europe. It was implemented into Ukrainian legislation on 01 January 1998. It is committed to maintaining an optimal balance between the municipality and local self-government. This is the reference point promoted by the European Charter, which is referred to by the current legislation of Ukraine.

Європейська хартія місцевого самоврядування, прийнята в Страсбурзі 15 жовтня 1985 року державами-членами Європейської Ради, стала основою для міжнародного регулювання самоврядування в прогресивних країнах, які є членами Ради Європи. Це було впроваджено в законодавство України 01 січня 1998 року. Він зобов’язаний підтримувати оптимальний баланс між муніципалітетом та місцевим самоврядуванням. Це орієнтир, пропагований Європейською хартією, на яку посилається чинне законодавство України.
Keywords: local self-government; the Constitution of Ukraine; the European Charter of Local Self-Government; unitarism and regionalism; the state; місцеве самоврядування; Конституція України; Європейська хартія місцевого самоврядування; унітаризм та регіоналізм; держава